Regulation of Dipeptidyl Peptidase-4, its Substrate Chemokines, and Their Receptors in Adipose Tissue of ob/ob Mice - Shin, Jihoon; Fukuhara, Atsunori; Onodera, Toshiharu; Yokoyama, Chieko; Otsuki, Michio; Shimomura, Iichiro (Hormone and Metabolic Research, 2017)
The physiological function of DPP-4 in proteolytic inactivation of incretins has been well established, however, there is limited information on the expression and the significance of DPP-4 in white adipose tissue with regard to obesity. The objective of the work was to reveal the expression and regulation of DPP-4 in adipocytes and compare the expression and activity of DPP-4 in white adipose tissue and several other organs such as the liver, muscle and kidney. We also investigated the gene expression levels of DPP-4 substrate chemokines, and their receptors in white adipose tissue. DPP-4 was mainly expressed in stromal vascular fraction (SVF), and downregulated in adipose tissue of ob/ob compared with C57BL6/J mice. Mimetic conditions of obese fat in vitro showed that differentiation of mouse primary preadipocytes into adipocytes was associated with marked downregulation of DPP-4 expression. Treatment with TNF-α or ROS even decreased DPP-4 expression in mouse primary adipocytes. Various DPP-4 substrate chemokines were expressed in white adipose tissue and regulated by obesity. The expression of receptors for DPP-4 substrate chemokines was markedly high and tightly regulated by obesity in white adipose tissue. Expression of DPP-4 was reduced in adipose tissues of ob/ob mice. Actions of several substrate chemokines might be potentiated by downregulation of DPP-4, synergistically with upregulation of chemokines and their receptors in adipose tissues of obese mice.
Keywords: DPP-4; obesity; differentiation; preadipocytes; chemokine